Probability, econometrics and truth : the methodology of econometrics - Keuzenkamp, Hugo A. (Cambridge University Press, 2000)
This book assesses the foundations and development of econometrics and sets out a basis for the reconstruction of the foundations of econometric inference by examining the various interpretations of probability theory which underlie econometrics.